Mineral nutrition of tropical legumes: IV concentration and accumulation in micronutrients in Leucaena leucocephala (LAM.) de Wit cv. Peru during a one year period - Silva, Denise Helu; Haag, Henrique Paulo (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
The tropical leguminous plants are known as a high quality protein source and in some cases even as wood producers when dealing with the arbustive types. The leucena (Leucaena leucocephala (Lam.) de Wit cv. Peru) was noticed as a very promising species to the Brazilian cattle production, and this fact leads to the setting of a field experiment in order to know its nutrient demands. The experiment was carried out to obtain data for analysis of growth, concentration and extraction of micronutriets (B, Cu, Fe, Mn, Zn). From the obtained data it was possible to verify that the Mn concentration decreases in leaves and stem along the plant life. On the other hand, the age of the plant did not affect the B and Fe concentrations in the leaves. When the plants were 360 days old, corresponding to the highest dry matter production period, the following contents in the leaves and stem were observed: Plants with 360 days also showed the micronutrient accumulations in the following order: Fe >; Zn >; B >; Mn >; Cu